Recovery of Diabetic Rats After Physical Exhaustion: Kinetic Alterations in Muscle Inflammation and Muscle-Signaling Proteins to Atrophy and Hypertrophy - Bortolon, José Ricardo; Murata, Gilson Masahiro; Borges, Leandro; Weimann, Eleine; Silva, Maysa Braga Barros; Dermargos, Alexandre; Hatanaka, Elaine (Frontiers in Physiology, 2020)
The complexity of the adaptive response of diabetics to intense exercise is still poorly understood. To optimize exercise interventions in diabetics, the chronology of inflammatory mediators in muscle and the signalling involved in muscle hypertrophy/atrophy must be understood. Herein, we studied the kinetic inflammatory profile and cellular signalling pathways modulated by physical exhaustion after the induction of type 1 diabetes by streptozotocin in rats. Soleus muscle samples were obtained from diabetic and control groups at the following moments: baseline (no exercise); immediately after exhaustive exercise; and at 2 h, 24 h, 48 h, and 72 h after a treadmill exhaustive exercise. Kinetic production of cytokines and kinetic activation of proteins related to muscle synthesis (p70S6K and Akt) and degradation (GSK3, MuRF1, and MAFbx) were measured in the soleus muscle. We observed that the muscle TNF-α (0.9-fold; p=0.0007), IL-1β (0.8-fold; p=0.01), IL-6 (0.8-fold; p=0.0013), L-selectin (1.0-fold; p=0.0019), and CINC-2α/β (0.9-fold; p=0.04) levels were higher in almost all stages of the study in the diabetic animals compared with the control group. Our data showed that exhaustive exercise decreased MAFbx expression in diabetic animals compared to the control group in a time-dependent manner. The decreased activation ratios of MAFbx were followed by a decrease in TNF-α, IL-1β, and IL-6 levels. p70S6k phosphorylation was also decreased in the diabetic group compared to the control group after physical exhaustion. Regarding the activation of proteins related to muscle synthesis and degradation, we found that the alterations induced by exhaustive exercise in the diabetic rats might involve pathways related to synthesis and muscle breakdown. Moreover, after an exhaustive exercise session, the recovery of the inflammatory response in the diabetic animals was slower than that in the control rats while the return of inflammatory cytokines to baseline levels was more effective in the diabetic animals.